Karyotype differentiation patterns in species of the subfamily Scarabaeinae (Scarabaeidae, Coleoptera) - Cabral-de-Mello, Diogo Cavalcanti [UNESP]; de Oliveira, Sarah Gomes; Ramos, Ituza Celeste; de Moura, Rita de Cassia (Pergamon-Elsevier B.V. Ltd, 2008)
The aim of this study was to describe the karyotype of species belonging to the subfamily Scarabaeinae (Coleoptera, Scarabaeidae) and to compile the conventional cytogenetic data available in the literature for this group. The karyotypes of ten species belonging to the tribes Canthonini, Coprini, Onthophagini and Phanaeini were analyzed by conventional staining. Eight of these species were described for the first time (Canthon aff carbonarius, Canthon chalybaeus, Coprophanaeus dardanus, Deltochilum aff amazonicum, Dichotomius geminatus, Oxysternon silenus, Phanaeus chalcomelas and Malagoniella aff astyanax) and two were redescribed (Diabroctis mimas and Digitonthophagus gazella) since their karyotypes differed from those previously published in the literature. Four species studied showed a diploid number of 2n = 20 and a parachute type sex determining system and the karyotype was 2n = 20,Xy in two species and 2n = 18,Xy(p), 2n = 19,X0,2n = 12,XY and 2n = 14,neoXY in one each. The chromosome morphology of the different species varied, with the observation of metacentric, submetacentric, subacrocentric and acrocentric chromosomes. The X chromosome was predominantly meta or submetacentric in the species analyzed, whereas the y chromosome presented two arms or was punctiform. In conclusion, the subfamily Scarabaeinae comprises 120 species analyzed cytogenetically, and are observed the occurrence of five chromosome rearrangements (autosome-autosome and X-autosome fusions, pericentric inversions, fissions and loss of the y chromosome) that are related to the chromosome variability and evolution in the group. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chromosome evolution; Chromosome rearrangement; Chromosome variability; Karyotype; Sex determining system